Osteoinductivity and Antibacterial Properties of Strontium Ranelate-Loaded Poly(Lactic-co-Glycolic Acid) Microspheres With Assembled Silver and Hydroxyapatite Nanoparticles - Mao, Zhenyang; Li, Yang; Yang, Yunqi; Fang, Zhiwei; Chen, Xuan; Wang, Yugang; Kang, Jian; Qu, Xinhua; Yuan, Weien; Dai, Kerong; Yue, Bing (Frontiers in Pharmacology, 2018)
Abstract: Bone-related infection rates are 4-64% in long open bone fractures and nearly 1% in joint-related surgeries. Treating bone infections and infection-related bone loss is very important. The present study prepared strontium ranelate (SR)-loaded poly(lactic-co-glycolic acid) (PLGA) microspheres (PM) with assembled silver nanoparticles (AgNPs) and hydroxyapatite nanoparticles (HANPs) (SR-PM-Ag-HA) through a novel solid-in-oil nanosuspension (S/O/N) method to achieve osteoinductivity and antibacterial properties. We evaluated the microstructure, drug release, biocompatibility, osteoinductivity, and antibacterial activity in vitro. The microspheres showed a stable shape and size. The cumulative drug release reached a maximum of 90% after 22 d. All groups loaded with SR enhanced MC3T3-E1 cell proliferation to a greater degree than pure PM. The osteoinductivity behavior was investigated by ALP staining and real-time PCR of osteogenic differentiation marker genes. The antibacterial activity was evaluated using antibacterial ability and biofilm formation assays. SR-PM-Ag-HA greatly enhanced osteogenic differentiation and showed excellent antibacterial properties. These results indicated that SR-PM-Ag-HA could be biocompatible and suitable for drug delivery, osteoinduction, and antibiosis, and therefore, have potential applications in the treatment of bone-related infections and promotion of bone formation at infected sites.